Losartan Improves Palmitate-Induced Insulin Resistance in 3T3-L1 Adipocytes Through Upregulation of Src Phosphorylation - Tian, X.; Ye, M.; Cao, Y.; Wang, C. (Experimental and Clinical Endocrinology & Diabetes, 2017)
Angiotensin II type 1 receptor blocker losartan has shown strongly anti-insulin resistance properties in vivo and in vitro; however, the underlying mechanisms are poorly understood. In this study, we demonstrate that losartan administration increased phosphorylation of Akt and its downstream Akt substrate of 160 kDa (AS160), enhanced plasma membrane translocation of glucose transporter type 4 (GLUT4), and increased glucose uptake, along with increased Src phosphorylation as well as reduced expression of docking protein 1(DOK1) in palmitate-treated 3T3-L1 adipocytes. The beneficial impacts of losartan on insulin signaling were diminished in Src-deficient 3T3-L1 adipocytes. In addition, suppressed expression of DOK1 by losartan was abolished by Src knockdown. Our results suggest that anti-insulin resistance ability of losartan is mediated by Src/DOK1/Akt pathway.